Systematic Literature Review of Islamic Insurance Research: Thematic Analysis and Scopus-Based Insights - Kusumaningtyas, Fitri Nurjanah; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2023)
The objective of this study is to undertake a thorough examination of research advancements in the domain of Islamic insurance. This study uses content analysis methodologies to discern the prevailing themes within the chosen subject matter. The methodology employed in this systematic literature review involves extracting research data from prominent international databases, such as Scopus. This review focuses on content analysis and identifying recurring themes within the collected data. The study's findings indicate that research on Islamic insurance predominantly focuses on several topics, such as the insurance system, corporate social responsibility, and agricultural economics. This study adds significantly to the scholarly community by shedding light on overlooked aspects of Islamic insurance, promoting advancements in research within this domain. In addition, the findings of this study can offer valuable insights for scholars seeking to delve into these matters and enhance the body of knowledge in the realm of Islamic insurance.